The Law of Inheritance of Monetized YouTube Channels in Indonesia: Exploring Legal Theory and Crowdfunding Theory - Dwi Fidhayanti; Zaky Ramadhan; Syabbul Bachri (Istinbath : Jurnal Hukum, 2025)
YouTube has become a non-physical, inheritable asset, as it carries economic value and can be transferred through inheritance. This study examines the division and management of royalties from monetized YouTube channels under Indonesian positive law for heirs. It also analyzes the technical distribution and management of royalties according to crowdfunding theory. This research adopts a normative juridical approach, drawing on legislative and conceptual frameworks. Primary legal materials include Law No. 28 of 2014 concerning Copyright and the Compilation of Islamic Law. The study's findings reveal that 1) under copyright law, royalty management for monetized YouTube channels containing musical content can be conducted through a collective management institution, while there is no specific institution managing video content royalties for heirs. The Compilation of Islamic Law suggests an amicable settlement as an alternative resolution if Articles 176-182 and 185 are not applicable; 2) Crowdfunding can be applied by consolidating the shares or portions of each heir within a single monetized YouTube channel, managed by one heir as the content creator. Royalties earned from the channel are then distributed to each heir based on the share percentages outlined in Articles 176-182 of the Compilation of Islamic Law.